Impact of Jharkhand State Cooperative Milk Producers' Federation on Socioeconomic Status of Dairy Farmers - Mandi, Kalyan; Chakravarty, Ritu; Ponnusamy, K.; Kadian, K. S.; Dixit, A. K.; Singh, Magan; Misra, A. K. (Indian Journal of Extension Education, 2022)
The paper assesses the impact of membership of dairy cooperative i.e. Jharkhand State Cooperative Milk Producers' Federation (JMF) on the performance of dairy production systems using propensity score matching techniques. Dairy cooperative members differed significantly from non-members in terms of outcome variables. The mean difference valueÂ Â explained that the socio-economic condition of members was better than non-members. The findings revealed that membership of JMF contributes towards improving yields of dairy animals, net dairy income, and also, to household milk consumption. The non-members reaped better price for the milk in the wet market as compared to the members. Nonetheless, the member-producers recorded higher proportion of milk sale as compared to the nonmembers which also indicated their intensity of market participation. These results indicate towards the need to improve dairy farmers' linkages through cooperatives or other such institutions for their socio-economic development.